Implementation of the Roskill Model in the Mechanism for Handling Large-Scale Fraud Crimes in Indonesia? - Jacob, Pricilla Amelinda; Nelson, Febby Mutiara (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2024)
The necessity for a specialized unit to address large-scale fraud crimes is grounded upon the increasing prevalence of such crimes and the substantial losses incurred by victims. Large-scale fraud crimes, characterized by money laundering as a follow-up crime, have become increasingly challenging to prosecute, with the assets derived from these crimes becoming harder to trace due to globalization. Disproportionate restitution proportions reflect the challenges in tracing criminal assets. There exists a strong correlation between successfully traced assets and the amount returned to victims of these crimes. The proposal to utilize the Roskill Model in handling large-scale fraud crimes is based on an economic analysis approach to its suitability in law enforcement efforts, while maintaining a focus on the restitution rights of victims without compromising the efficiency of the criminal justice system. The Roskill Model can internalize the external costs generated by these crimes. This model has been implemented in various countries, including the UK, New Zealand, and India, demonstrating its effectiveness and efficiency in addressing serious and complex financial crimes. The Roskill Model's applicability in Indonesia is considered feasible, guided by principles of swift, simple, and cost-effective justice, along with efforts to reform Indonesian criminal procedural law for greater efficiency. This research employs an economic analysis of law (EAL) with an interdisciplinary approach encompassing both legal and economic disciplines. Additionally, the study includes a comparative legal analysis with the UK (common law system) and Switzerland (civil law system).